Odpowiedzi

2010-04-06T17:45:53+02:00
[(2 2/7) :(-4/21) - 3,125 *3,2]+[-1 ⅔-0,65:(-2⅙)]=[(16/7)*(-21/4)- 3⅛*3,2]+[-(5/3)+0,65*(6/13)]=[12-(25/8)*(16/5)]+[-(5/3)+(13/20)*(6/13)]=[12-10]+[-(5/3)+0,3]=2-1⅔+0,3=2,3-1⅔=1,3-⅔=(13/10)-⅔=(39/30)-(20/30)=19/30
Najlepsza Odpowiedź!
2010-04-06T18:06:49+02:00
[(2 2/7) :(-4/21) - 3,125 ×3,2]+[-1 ⅔-0,65:(-2⅙)]=[(16/7)×(-21/4)- 3⅛×3,2]+[-(5/3)+0,65×(6/13)]=[12-(25/8)*(16/5)]+[-(5/3)+(13/20)*(6/13)]=[12-10]+[-(5/3)+0,3]=2-1⅔+0,3=2,3-1⅔=1,3-⅔=(13/10)-⅔=(39/30)-(20/30)=19/30